2019
DOI: 10.1029/2018jg004743
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Composition of Humic Substances Isolated From Yedoma Permafrost and Alas Cores in the Eastern Siberian Arctic as Measured by Ultrahigh Resolution Mass Spectrometry

Abstract: Ongoing climate change is making the large pool of organic matter (OM) stored in Arctic permafrost vulnerable to mobilization; thus, garnering a deeper understanding of molecular transformations within the abundant pool of soil OM, specifically humic substances, is crucial. Here we present the first high-resolution mass-spectrometry examination of molecular compositions of humic acid (HA) and fulvic acid (FA) isolated from organic-rich deep yedoma (Pleistocene age ice-rich permafrost) and alas (thermokarst dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…To date, extended literature has been produced on the application of FT-ICR MS to NOM and its fractions, mostly in relation to dissolved organic matter (DOM) (Brown and Rice, 2000;Kujawinski, 2002;Stenson et al, 2002;Sleighter and Hatcher, 2007;Remucal et al, 2012;Lv et al, 2016). But, when it comes to the terrestrial soil organic matter (SOM) and its fractions, only a few publications arise (Kramer et al, 2004;Ohno et al, 2010;Piccolo et al, 2010;Ohno and Ohno, 2013;Zherebker et al, 2019), whereas investigations on other sources such as ores or compost are rare. A recent innovative approach has been incorporated in the pipeline of the studies on biologically active metabolites, where molecular formulas obtained by FT-ICR MS were sourced from public online databases with valuable results that helped gathering insights into the chemistry of HS (Fedoros et al, 2018;Orlov et al, 2019;Zhernov et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…To date, extended literature has been produced on the application of FT-ICR MS to NOM and its fractions, mostly in relation to dissolved organic matter (DOM) (Brown and Rice, 2000;Kujawinski, 2002;Stenson et al, 2002;Sleighter and Hatcher, 2007;Remucal et al, 2012;Lv et al, 2016). But, when it comes to the terrestrial soil organic matter (SOM) and its fractions, only a few publications arise (Kramer et al, 2004;Ohno et al, 2010;Piccolo et al, 2010;Ohno and Ohno, 2013;Zherebker et al, 2019), whereas investigations on other sources such as ores or compost are rare. A recent innovative approach has been incorporated in the pipeline of the studies on biologically active metabolites, where molecular formulas obtained by FT-ICR MS were sourced from public online databases with valuable results that helped gathering insights into the chemistry of HS (Fedoros et al, 2018;Orlov et al, 2019;Zhernov et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, AI is the most conservative aromatic system approximation. Despite known limitations of these indices (especially AI mod ), they currently serve as major structural parameters in many geochemical studies of NOM/HS. The use of AI may thus lead to false conclusions about the aromatic character of molecules for structurally constrained samples. For example, we have recently shown that molecules with the same low AI value (e.g., 0.3) may correspond to isomers with and without aromatic rings depending on the geochemical origin …”
mentioning
confidence: 99%
“…However, the formulae list detected for coal HA (CHA-h 36 ) was not unequivocally assigned to the CHA sample from the database: based on top-ranked 9000 FDs, SHA-Ctk suggested the lowest FDCEL distance, but CHA would be a second choice. The unconventional result was also obtained for FA samples, which were isolated from the permafrost soil 37 . Supposedly, FA1-Y-15 and FA2-Y-15 are represented by the low-transformed organic compounds well conserved under the ice shield.…”
Section: Databasementioning
confidence: 74%
“…Dataset I includes formulae lists acquired for SRFA with various ionization techniques: ESI (SRFA-r 24 , SRFA-t 11 , SRFA-u 25 ), LDI (SRFA-s 26 ), PSI (SRFA-v 25 ), PSCI (SRFA-w 25 ). Dataset G for geochemical application verification includes various formulae lists: SLNOM-XAD, SLNOM-PPL 27 ; PRNOM, AHF-RPP-10, AHF-RPP-11, AHF-RK5P-10, AHF-RK6P-10, AHF-AOP-10 31 ; SDOM-GF 33 ; PHA-TTL 35 ; coal humic acid CHA-h has been described elsewhere 36 and it has been analyzed via Bruker Daltonics 12 Tesla Apex Qe FTICR-MS, housed at the College of Sciences Major Instrumentation Cluster (COSMIC) at Old Dominion University; FA1-Y-15, FA2-Y-15 37 .…”
Section: Datamentioning
confidence: 99%